2001
DOI: 10.1128/aac.45.8.2224-2228.2001
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-Lactamases in Clinical Pseudomonas Isolates in Taiwan and Identification of VIM-3, a Novel Variant of the VIM-2 Enzyme

Abstract: A total of 209 clinical isolates of Pseudomonas (193 Pseudomonas aeruginosa, 10 P. putida, 4 P. stutzeri, and 2 P. fluorescens isolates) with reduced susceptibilities to imipenem and/or ceftazidime were subjected to PCR assays with primers specific for bla IMP-1 , bla IMP-2 , bla VIM-1 , and bla VIM-2 and sequence analysis to identify the metallo-␤-lactamases (MBLs) prevalent among these organisms in Taiwan; and 21 isolates gave positive results. Five isolates including two P. putida and three P. stutzeri isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
1
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(166 citation statements)
references
References 31 publications
3
144
1
18
Order By: Relevance
“…9 Our investigation accords with other studies. 10,11,12 Our data deviates from reports of two studies by El-Kholy et al 13 and Pitout et al 14 issued higher rates of MBLs among P. aeruginosa that were (62%) and (46%) respectively. MBLs among P. aeruginosa have been increasingly recognized from clinical isolates worldwide; for example (55.2%) in Egypt and (66.7%) in Saudi Arabia, 15 in Brazil (76.7%), 16 in France (46%), 17 in India (13.6%), 18 in Iran (20%), 19 and in Korea(24.2%).…”
Section: Discussioncontrasting
confidence: 57%
“…9 Our investigation accords with other studies. 10,11,12 Our data deviates from reports of two studies by El-Kholy et al 13 and Pitout et al 14 issued higher rates of MBLs among P. aeruginosa that were (62%) and (46%) respectively. MBLs among P. aeruginosa have been increasingly recognized from clinical isolates worldwide; for example (55.2%) in Egypt and (66.7%) in Saudi Arabia, 15 in Brazil (76.7%), 16 in France (46%), 17 in India (13.6%), 18 in Iran (20%), 19 and in Korea(24.2%).…”
Section: Discussioncontrasting
confidence: 57%
“…22 Previous studies demonstrated that IMP and VIM producer genes of MBLs were also common in Asian studies. [23][24][25] VIM type was also highly prevalent in Turkey. 26 In previous studies in Egypt and Taiwan, VIM-2 demonstrated the highest outbreak among imipenem-resistant P. aeruginosa strains.…”
Section: Discussionmentioning
confidence: 99%
“…VIMtype enzymes have since been found in Greece (11) and in Turkey and Portugal (2), including the new variants VIM-4 and VIM-5 (GenBank accession number AY144612). The other focus for VIM-type enzymes appears to be the Far East, notably, VIM-2 in Korea (6) and VIM-3 in Taiwan (15). VIM-2, VIM-3, and VIM-6 appear to form a cluster (with at least 99.2% amino acid identity within the cluster) whose amino acid sequences differ from those of the other VIM enzymes by about 10% (Fig.…”
Section: Vol 48 2004 Notesmentioning
confidence: 99%
“…DNA probes were synthesized by using the PCR DIG Probe Synthesis kit (Roche Diagnostics GmbH, Mannheim, Germany) and primers specific for bla IMP-1 and bla VIM-2 , as described by Yan et al (15). DNA extracts from P. putida DB33824/00 and DU25151/00 served as templates.…”
mentioning
confidence: 99%